Transgenic Mice Overexpressing Renin Exhibit Glucose Intolerance and Diet-Genotype Interactions - Fletcher, Sarah J.; Kalupahana, Nishan S.; Bejnood, Morvarid; Kim, Jung Han; Saxton, Arnold M.; Wasserman, David; De Taeye, Bart; Voy, Brynn; Quignard-Boulange, Annie; Moustaid-Moussa, Naima (Frontiers in Endocrinology, 2013)
Numerous animal and clinical investigations have pointed to a potential role of the renin-angiotensin system (RAS) in the development of insulin resistance and diabetes in conditions of expanded fat mass. However, the mechanisms underlying this association remain unclear. We used a transgenic mouse model overexpressing renin in the liver (RenTgMK) to examine the effects of chronic activation of RAS on adiposity and insulin sensitivity. Hepatic overexpression of renin resulted in constitutively elevated plasma angiotensin II (4-6-fold increase vs. wild type). Surprisingly, RenTgMK mice developed glucose intolerance despite low levels of adiposity and insulinemia. The transgenics also had lower plasma triglyceride levels. Glucose intolerance in transgenic mice fed a low-fat diet was comparable to that observed in high fat-fed wild type mice. Glucose intolerance was exacerbated by high-fat feeding, only in female transgenic mice. These studies demonstrate that overexpression of renin and associated hyperangiotensinemia impair glucose tolerance in a diet-dependent manner and further support a consistent role of RAS in the pathogenesis of diabetes and insulin resistance, independent of changes in fat mass.